1979
DOI: 10.1097/00006842-197906000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Disturbance and Cognitive Deficits in Hyperthyroidism

Abstract: Assessment of cognitive and emotional variables in 19 females with hyperthyroidism was made pretreatment, at 3 weeks, and after euthyroidism was established. A matched group of normal controls was similarly tested. Group differences on cognitive measures did not reach statistical significance, but cognitive deficits and symptoms of emotional disorder were significantly associated with the severity of thyroid toxicity previous to treatment. Measures of cognitive function and personality features moved towards c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
3

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 0 publications
3
24
0
3
Order By: Relevance
“…High T3 levels seem to worsen subjec tive well-being and alertness also in the absence of signifi cant bodily complaints. This finding is consistent with earlier studies in hyperthyroid patients who are described as being more depressive, anxious, and emotionally irrita ble than healthy subjects [6,8,9, 17], Fatigue as a conse quence of enhanced T3 levels seems quite unexpected as T3 induces higher CNS excitability [18] as reflected in electroencephalographic (EEG) parameters like an in creased alpha frequency [19]. However, activation which is caused by T3 levels beyond the normal physiological range may probably result in restlessness and sleep distur bance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…High T3 levels seem to worsen subjec tive well-being and alertness also in the absence of signifi cant bodily complaints. This finding is consistent with earlier studies in hyperthyroid patients who are described as being more depressive, anxious, and emotionally irrita ble than healthy subjects [6,8,9, 17], Fatigue as a conse quence of enhanced T3 levels seems quite unexpected as T3 induces higher CNS excitability [18] as reflected in electroencephalographic (EEG) parameters like an in creased alpha frequency [19]. However, activation which is caused by T3 levels beyond the normal physiological range may probably result in restlessness and sleep distur bance.…”
Section: Discussionsupporting
confidence: 93%
“…Whybrow et al [4] found hyperthyreotics performing poorer in tests measuring anticipatory thinking, mental alertness, and visuomotor speed. Another study [6] de tected subtle abnormalities in acute untreated hyperthy roid patients which were significantly correlated with peak T4 level prior to treatment. Correlations were highest with performance in tasks requiring memory and concen tration.…”
Section: 5] Examination Of Cognitive Functions In Hyper Thyroid Pmentioning
confidence: 98%
“…It is known that hyperthyroidism leads to involvement of the central nervous system, including clinical symptoms such as reduced concentration and memory performance, nervousness, irritability, and tremulousness [7,14,15] . However, these studies have mostly been obtained in clinical populations and thus a number of confounds, such as the direct impact of autoimmune disease on the brain, have to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…A má aderência pode ser conseqüência do menor nível de atenção e da labilidade emocional que são sintomas freqüentes nos pacientes com doença de Graves (3,17). Outras causas que comprometem a aderência neste tipo de tratamento são a ingestão de um número elevado de comprimidos, a ocorrência de efeitos colaterais (embora este fator não tenha sido relevante no grupo estudado) e o fato da doença ser mais prevalente no sexo feminino, considerado mais indisciplinado e menos aderente à medicação (18,19).…”
Section: Eutiroidismo No Graves: Tempo E Custounclassified